Development and validation of a scale to measure the simulation-based learning outcomes in teacher education - Levin, Orna; Frei-Landau, Rivi; Goldberg, Chen (Frontiers in Education, 2023)
Introduction Simulation-based learning (SBL) is gradually being integrated into the field of teacher education. However, beyond specific content acquisition, comprehensive knowledge of SBL outcomes is limited. This research aimed to systematically develop a scale to measure SBL outcomes in teacher education. Methods A mixed-methods sequential exploratory design was implemented, to develop the Simulation-based Learning Outcomes in Teacher Education (SLOTE) scale. Data were collected in two phases: a qualitative (N = 518) phase followed by a quantitative (N = 370) phase. Results The qualitative analysis revealed three overarching themes: communication skills, collaborative-learning-related insights, and emotional self-awareness. The scale items were prepared based on key quotes from the qualitative data. To define, quantify, and validate learning outcomes of SBL in teacher education, EFA and CFA were used to test the relationship among 29 items of the scale. Discussion The study provides a theoretical conceptualization of SBL’s multifaceted learning outcomes in teacher education. These findings allow for a better understanding of the observers’ role in SBL, suggesting that enacting the simulation is not inherently more emotionally demanding and, consequently, participants in both roles are apt to benefit equally from the experiential learning afforded by the SBL process. Theoretical and practical implications of using SBL in teacher education are discussed.